Liderança e motivação na Codinome Seguros na percepção dos seus colaboradores - Fernandes, Lucas Vinicius (2021)
Due to the current scenario in which we live, companies are increasingly improving their processes to gain competitiveness and bring a greater number of customers to their company. Therefore, developing leadership and employee motivation is essential for the company to develop and achieve its goals more quickly and efficiently, despite the technological world in which we live, human capital is still very important for companies to be able to to develop. Thus, this work aims to analyze the leadership and motivation of the company Codinome Seguros in the employees' perception. Regarding the methodology, a descriptive research was carried out through a case study, which was done in order to analyze the leadership and motivation points of the studied company. The results obtained through the survey resulted in a general way that the company has a good development in its leadership strategy and motivation of its employees, having effective leaders who have the ability to motivate and lead their employees, so it was obtained good results for most of the points although there are some points of attention for improvement so that they can develop further and not regress in any of the subjects.